Reliability and Validity of Tethered Swimming Lactate Minimum Test and Their Relationship With Performance in Young Swimmers - Kalva-Filho, Carlos Augusto; Toubekis, Argyris; Zagatto, Alessandro Moura [UNESP]; Ramos da Silva, Adelino Sanchez; Loures, Joao Paulo; Campos, Eduardo Zapaterra; Papoti, Marcelo (Human Kinetics Publ Inc, 2018)
Purpose: To test the reliability and validity of tethered swimming lactate minimum test in young swimmers. Methods: Lactate minimum test was performed twice to test the reliability (experiment 1; n = 13). In addition, the validity was investigated through lactate minimum test relationships with tethered swimming lactate threshold and peak force obtained during graded exercise test (experiment 2; n = 11). Finally, the correlations with mean speeds observed during 200-m (s200m) and 30-minute continuous efforts (s30min) were also analyzed (experiment 3; n = 15). In all experiments, the lactate minimum test began with 3-minute all-out effort to induce lactatemia, followed by an exhaustive graded exercise test. Results: The lactate minimum intensity and mean force during the entire 3-minute all-out effort (MF) showed high reliability (coefficient of variation < 8.9% and intraclass correlation coefficient > .93). The lactate minimum intensity was not different compared with lactate threshold (P = .22), presenting high correlations (r = .92) and agreement (95% limits of agreement = +/- 7.9 N). The mean force during the entire 3-minute all-out effort was similar to peak force obtained during graded exercise test (P = .41), presenting significant correlations (r = .88) and high indices of agreement (95% limits of agreement = +/- 11.3 N). In addition, lactate minimum test parameters correlated both with mean speeds observed during 200-m (r > .74) and 30-minute continuous efforts (r > .70). Conclusion: Thus, tethered swimming lactate minimum test can be used for training recommendations and to monitor aerobic adaptations in young swimmers.
Keywords: reproducibility; endurance capacity; aerobic evaluation; sports science